Drivers and barriers of process innovation in the EU manufacturing food processing industry: Exploring the role of energy policies - Federica De Maria; Annalisa Zezza (Bio-based and Applied Economics (BAE), 2020)
This paper investigates the driving forces that can promote or impede process innovation adoption in the European food manufacturing industry. The study uses a logit model applied to Community Innovation Survey (CIS) data containing information on innovation at the industry level for 15 EU Member States. Results suggest the relevance of many factors, internal and external to the enterprise, such as size and organization of business practices on one hand, and networking activities and cooperation agreements within the supply chain on the other hand. We also focus on energy policy variables as process innovation determinants. Energy policies implementation, energy price and the availability of public funds, show a significant impact on process innovation adoption in the European food processing industry.
Keywords: L66; O3; Q4; Q16; 330; Environmental Regulation; Energy policy; Innovation; Cooperation activities; Food manufacturing industry; EU